Temporal variation of green macroalgal assemblage on Porphyra aquaculture rafts in the Subei Shoal, China. (20th September 2015) - Fan, Shiliang; Fu, Mingzhu; Wang, Zongling; Zhang, Xuelei; Song, Wei; Li, Yan; Liu, Guangxing; Shi, Xiaoyong; Wang, Xiaona; Zhu, Mingyuan
Abstract: Previous studies showed that Ulva prolifera caused green tides in the Yellow Sea were very possible from the facilities of Porphyra aquaculture. To confirm the origin of green algae, the assemblage of fouling macroalgae growing on rafts were investigated from early March to the middle of May across the growing season. The results showed that the fouling green macroalgae increased rapidly and reached to the maximum in biomass during mid-May. Six species, including Blidingia sp., U . prolifera, Ulva linza, Ulva compressa, Ulva intestinalis and Ulva clathrata were identified from the rafts. In early March, the dominant species were U . compressa, U . intestinalis and U . clathrata ; while they shifted to Blidingia sp. and U . prolifera in late March to middle May. This study indicated that the changes in sea temperature might affect the nutrient uptake rate of the green macroalgae, and then affect the temporal variation in the raft-fouling green macroalgae. The biomass of U . prolifera was sufficient to seed a massive green tides, based on its high growth rate. Graphical abstract: Highlights: Six fouling green macroalgal species coexisted on the rafts of the Subei Shoal. The fouling green macroalgal assemblage varied over time. Nutrients and temperature played important roles in the variation.